Changes During the Processing of Duck Meatballs Using Different Fillers after the Preheating and Heating Process - Putra, A.A.; Huda , N.; Ahmad, R. (International Journal of Poultry Science, 2010)
In the process of manufacturing duck meatballs, three different fillers (corn, sago and cassava) are used as representatives of grain, root and palm sources of fillers. Different stages of duck meatball processing, such as dough, pre-heating and heating, were analyzed to further the research on the manufacturing process of duck meatballs. In this study, the nutritional contents, physicochemical characteristics and sensory attributes are collected. In general, there were no significant differences (p>0.05) among the fillers in the characteristics that we examined. However, there were significant differences (p